2020
DOI: 10.1002/nop2.443
|View full text |Cite
|
Sign up to set email alerts
|

Newly graduated registered nurses' self‐assessed clinical competence and their need for further training

Abstract: Aim To explore and describe changes in self‐assessed clinical competence and the need for further training among newly graduated Registered Nurses during their first 15 months of professional work in acute care hospital settings. Design Quantitative longitudinal design. Methods The 50‐item Professional Nurse Self‐Assessment Scale of clinical core competencies II was used. A total of 45 newly graduated Registered Nurses answered the questionnaire at four different occasions. Data were collected after 2, 5, 9 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 57 publications
0
16
1
9
Order By: Relevance
“…In the process of developing clinical competence that can be applied to complex patient situations, this study showed that reflection gave NGRNs the opportunity to learn how to handle the demands of nursing complex patient situations. NGRNs' clinical competences in acute care hospital settings increased over time, with a significant difference seen between 9–15 months (Willman, Bjuresäter, & Nilsson, 2020b). Experience alone does not automatically lead to increased competence, in order for clinical competence to develop and transit through one competence stage to the next, intellectual and critical thinking is essential (Benner, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of developing clinical competence that can be applied to complex patient situations, this study showed that reflection gave NGRNs the opportunity to learn how to handle the demands of nursing complex patient situations. NGRNs' clinical competences in acute care hospital settings increased over time, with a significant difference seen between 9–15 months (Willman, Bjuresäter, & Nilsson, 2020b). Experience alone does not automatically lead to increased competence, in order for clinical competence to develop and transit through one competence stage to the next, intellectual and critical thinking is essential (Benner, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to competence development and lifelong learning, the results in this study show the importance of self‐reflection as a way to further develop oneself, and this has also been shown in other studies (Forsman et al., 2019; Nilsson et al., 2019). Yet, the ability to think critically decreased after 9–15 months of clinical practice among NGRNs (Willman et al., 2020b). Possible reasons for a negative development in critical thinking include that NGRNs lack time for reflection, the lack of experienced RNs to support them and give new perspectives and the lack of possibilities for NGRNs to meet patients.…”
Section: Discussionmentioning
confidence: 99%
“…The development process of the PROFFNurse SAS I and II are described in Finnbakk et al (2015) (version I) [ 20 ] and Wangensteen et al (2018) (version II) [ 21 ]. The PROFFNurse SAS II used in the present study was developed ahead of a study among postgraduate nurses [ 21 ] and has also been used in studies by Taylor et al 2020 [ 32 ], and Willmann et al (2020) [ 33 ]. The questionnaire consists of 50 items and asks for responses on self-assessment of: a) competence (A-scale) and b) need for further training (B-scale).…”
Section: Methodsmentioning
confidence: 99%
“…In this complexity, the supervisory role of RNs and IDNs will be even more essential to support the education of competent newly graduated candidates [ 22 ]. As RN and IDN educators (all female, one with a Ph.d. and one pofessor), with several years of clinical experiences, to our knowledge few studies have explored RN and IDN supervisors’ perspectives on supervision across primary- and hospital healthcare services and also across RN and IDN education programs.…”
Section: Introductionmentioning
confidence: 99%